Research on Energy Storage Optimization Configuration in Integrated Energy System. Issue 1 (1st February 2022) - Mao, Cui; Chen, Yuping; Xv, Danning; He, Hongying; Shen, Hekun; Cai, Chengcong; Lu, Xuanyi
Abstract: Integrated Energy System (IES) is an important part of the ISTEM, which is an important part of IES, which solves a variety of energy storage, gas, electricity, heat, cold, cold, etc., as an important part of IES. This paper proposes a wide range of integrated energy storage optimization configuration models for multiple IES architectures, and analyzes the versatility of the model. First, the establishment of a general model of IES can cover various specific structures of IES; secondly, the integrated energy storage optimization configuration model is established on the basis of the IES universal model, so that the configuration model can be applied to a variety of IES architectures. The model is the smallest annual value of the annual value of the system life cycle, decision-making various energy storage configuration capacity and power; finally, in a commercial building IES, an altruistic analysis is carried out, and the optimized configuration model is in other scenes. The versatility is analyzed, and the results show that the model can be applied to the IES of the various architectures, solve the optimized configuration problem of integrated energy storage in different scenarios, and has versatility.